2001
DOI: 10.1007/pl00000829
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol impairs insulin-stimulated mitochondrial function in cerebellar granule neurons

Abstract: Ethanol impairs insulin-stimulated survival and mitochondrial function in immature proliferating neuronal cells due to marked inhibition of downstream signaling through P13 kinase. The present study demonstrates that, in contrast to immature neuronal cells, the major adverse effect of chronic ethanol exposure (50 mM) in post-mitotic rat cerebellar granule neurons is to inhibit insulin-stimulated mitochondrial function (MTT activity, MitoTracker Red fluorescence, and cytochrome oxidase immunoreactivity). Ethano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
54
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 43 publications
3
54
0
Order By: Relevance
“…Cell density was determined by labeling the cultures with 10 µg/ml Hoechst H33342 in Tris-buffered saline (TBS), and measuring fluorescence (Ex360 nm/Em460 nm) in a Spectramax M5 microplate reader (Molecular Dynamics, Inc., Sunnyvale, CA). Mitochondrial function was measured using the 3-[4,5-dimethylthiazol-2-yl]-2,5-diphenyltetrazolium bromide (MTT) assay as previously described (de la Monte, Neely et al 2001). Absorbances were measured at 540 nm in Spectramax M5 microplate reader.…”
Section: Methodsmentioning
confidence: 99%
“…Cell density was determined by labeling the cultures with 10 µg/ml Hoechst H33342 in Tris-buffered saline (TBS), and measuring fluorescence (Ex360 nm/Em460 nm) in a Spectramax M5 microplate reader (Molecular Dynamics, Inc., Sunnyvale, CA). Mitochondrial function was measured using the 3-[4,5-dimethylthiazol-2-yl]-2,5-diphenyltetrazolium bromide (MTT) assay as previously described (de la Monte, Neely et al 2001). Absorbances were measured at 540 nm in Spectramax M5 microplate reader.…”
Section: Methodsmentioning
confidence: 99%
“…Previous experiments demonstrated that neuronal loss following ethanol exposure was mediated by apoptosis (8 -10) or mitochondrial dysfunction (10 -12), and recent studies correlated these adverse effects of ethanol to inhibition of growth factor-stimulated survival signaling (9,(11)(12)(13). In the developing CNS, insulin and insulin-like growth factor type 1 (IGF-1) 1 receptors are abundantly expressed (14 -16), and the corresponding growth factor-stimulated responses are critical mediators of neuronal growth, viability, energy metabolism, and synapse formation.…”
mentioning
confidence: 99%
“…In the developing CNS, insulin and insulin-like growth factor type 1 (IGF-1) 1 receptors are abundantly expressed (14 -16), and the corresponding growth factor-stimulated responses are critical mediators of neuronal growth, viability, energy metabolism, and synapse formation. Because insulin and IGF-1 signaling pathways are among the important targets of ethanol neurotoxicity in immature nervous system (9,13,17,18), neuronal loss associated with microencephaly in ethanol-exposed fetuses may be caused, in part, by ethanol inhibition of insulin/IGF-1-stimulated survival mechanisms.…”
mentioning
confidence: 99%
“…In addition, prefibrillar tau can aggregate into soluble neurotoxic oligomers that cause synaptic disconnection and neuronal death (106). Although the key steps leading to tau hyper-phosphorylation and aggregation, could be explained on the basis of brain insulin/IGF resistance (107)(108)(109)(110), due to the associated decreased signaling through phosphoinositol-3-kinase (PI3K), Akt (28,29), and Wnt/β-catenin (111), and increased activation of GSK-3β (112)(113)(114)(115)(116), tau hyper-phosphorylation mediated by other mechanisms such as increased activation of cyclin-dependent kinase 5 (cdk-5) and c-Abl kinases (117,118), and inhibition of protein phosphatases 1 and 2A (105,118,119), could lead to oxidative stress and neuro-inflammation, which are inhibitory to insulin/IGF signaling.…”
Section: Role Of Tau Pathology In the Pathogenesis Of Type 3 Diabetesmentioning
confidence: 99%